PENINGKATAN MINAT DAN HASIL BELAJAR MATEMATIKA MATERI SEGIEMPAT DAN SEGITIGA MENGGUNAKAN MODEL PEMBELAJARAN (PAIKEM GEMBROT) PADA PESERTA DIDIK KELAS VII-D MTs NEGERI SALATIGA - Esti Rahayuningtyas; Muhammad Istiqlal (Program Studi Tadris Matematika IAIN Salatiga, 2019)
This research aimed to increase the interest mathemathics learning and student achievement of class VII-D MTs N 1 Salatiga used PAIKEM Gembrot type.the types of research was Classroom Action Research (CAR). Research was conducted minimal two cycles action. Data wa collected by questionnair, observation, interview, test and documentation.result showed an increase student interest viewed from questionnair, observation, interview and test. Student achievement incresed to by 42,89 at pre-cycle to 85,53 in cycle I and incresed to 90,53 in cycle II. Therefore suggested to teachers use the PAIKEM Gembrot type to increase student interest and achievement.